PENGARUH RETURN ON ASSET, EARNING PER SHARE, NET PROFIT MARGIN TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR KELAPA SAWIT YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2017-2021 - Muhammad Faldi; La Hatani; Muh. Taufik; Putu Sumarniawati; Sabri Sabri (Jurusan Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Halu Oleo, 2023)
This study aims to examine and analyze the effect of Return On Asset, Earning Per Share and Net Profit Margin partially and simultaneously on stock prices in Palm Oil sector companies listed on the Indonesia Stock Exchange (IDX). ) years 2017-2021. Research approach with a quantitative approach. The sample in this study amounted to 11. The sampling technique in this study was to use purposive sampling, namely the technique of determining the sample with certain predetermined criteria. Then it was analyzed using multiple linear regression analysis with the help software . The results showed that partially Return On Assets have a significant effect on stock prices, Earning Per Share has no significant effect on changes in stock prices and Net Profit Margin has a significant negative effect on stock prices. Simultaneously Return On Assets, Earnings Per Share and Net Profit Margin have a significant effect on stock prices.